Galaxy cluster aperture masses are more robust to baryonic effects than 3D halo masses. Issue 4 (26th July 2022) - Debackere, Stijn N B; Hoekstra, Henk; Schaye, Joop
ABSTRACT: Systematic uncertainties in the mass measurement of galaxy clusters limit the cosmological constraining power of future surveys that will detect more than 10 5 clusters. Previously, we argued that aperture masses can be inferred more accurately and precisely than 3D masses without loss of cosmological constraining power. Here, we use the Baryons and Haloes of Massive Systems (BAHAMAS) cosmological, hydrodynamical simulations to show that aperture masses are also less sensitive to changes in mass caused by galaxy formation processes. For haloes with $m_200m, dmo \gt 10^{14} \, h^{-1} \, \mathrm{M_\odot }$, binned by their 3D halo mass, baryonic physics affects aperture masses and 3D halo masses similarly when measured within apertures similar to the halo virial radius, reaching a maximum reduction of $≈ 3 \, \mathrm{per\, cent}$ . For lower mass haloes, $10^{13.5} \lt m_200m, dmo / h^{-1} \, \mathrm{M_\odot }\lt 10^{14}$, and aperture sizes $\sim 1 \, h^{-1} \, cMpc$, representative of weak lensing observations, the aperture mass is consistently reduced less ($\lesssim 5 \, \mathrm{per\, cent}$ ) than the 3D halo mass ($\lesssim 10 \, \mathrm{per\, cent}$ for m 200m ). The halo mass reduction evolves only slightly, by up to 2 $\mathrm{per\, centage}$ points, between redshift 0.25 and 1 for both the aperture mass and m 200m . Varying the simulated feedback strength so the mean simulated hot gas fraction covers the observed scatter inferred from X-ray observations, we find that the aperture mass is consistently less biased than the 3D halo mass, by up to $2 \, $ $\mathrm{per\, centage}$ points at $m_200m, dmo = 10^{14} \, h^{-1} \, \mathrm{M_\odot }$ . Therefore, aperture mass calibrations provide a fruitful path to reduce the sensitivity of future cluster surveys to systematic uncertainties.